Climate change adaptation attributes across scales and inter-institutional networks: insights from national and state level water management institutions in India - Azhoni, Adani; Holman, Ian P.; Jude, Simon (Springer, 2024)
Effective climate change adaptation requires cohesive inter-institutional networks across different scales, facilitating the sharing of data, information, knowledge, and practices. However, the impact of adaptation attributes across scales is poorly understood due to limited focus on these networks. Based on interviews with 26 institutions operating at the national level (ION) in India and 26 institutions operating within a state (Himachal Pradesh) (IOS), this study analysed adaptation attributes and the inter-institutional networks across the two scales to understand its implications at different scales. IONs have a greater capacity (compared to IOS) to frame guidelines, standards and regulations for practitioners along with better accessibility to resources and information. When coupled with bridging institutions, this can enhance adaptive capacities at other scales. Conversely, learnings from low regret adaptive measures being implemented by IOS are opportunities for informing national policy strategies. While national adaptation strategies and goals can inspire adaptation at lower scales, the currently fragmented inter-institutional network in India reduces the passage and accessibility of data and information, creating a bottleneck for the smooth devolution of adaptation attributes. Recruitment and deployment practices for water officials further entrench silo attitudes, impeding essential data accessibility. Adaptation needs comprehensive networks across vertical, horizontal, and diagonal institutional connections to improve climate risk perception and strategy implementation. Policy measures should consider socio-institutional factors beyond legislative prescriptions.
Keywords: Adaptation; Barriers; Climate change; Cross-scale; Institutions; Water; 4101 Climate Change Impacts and Adaptation; 41 Environmental Sciences; Generic health relevance; 13 Climate Action; Meteorology & Atmospheric Sciences; 4104 Environmental management